64.1k views
2 votes
X³ = x² + 20x how do you solve this by factoring?

User Naeio
by
7.8k points

2 Answers

3 votes

Answer: x = 5

x = -4

x = 0

Step-by-step explanation:The first term is, x2 its coefficient is 1 .

The middle term is, -x its coefficient is -1 .

The last term, "the constant", is -20

Step-1 : Multiply the coefficient of the first term by the constant 1 • -20 = -20

Step-2 : Find two factors of -20 whose sum equals the coefficient of the middle term, which is -1 .

-20 + 1 = -19

-10 + 2 = -8

-5 + 4 = -1 That's it

Step-3 : Rewrite the polynomial splitting the middle term using the two factors found in step 2 above, -5 and 4

x2 - 5x + 4x - 20

Step-4 : Add up the first 2 terms, pulling out like factors :

x • (x-5)

Add up the last 2 terms, pulling out common factors :

4 • (x-5)

Step-5 : Add up the four terms of step 4 :

(x+4) • (x-5)

Which is the desired factorization A product of several terms equals zero.

When a product of two or more terms equals zero, then at least one of the terms must be zero.

We shall now solve each term = 0 separately

In other words, we are going to solve as many equations as there are terms in the product

Any solution of term = 0 solves product = 0 as well. Solving x2-x-20 = 0 by Completing The Square .

Add 20 to both side of the equation :

x2-x = 20

Now the clever bit: Take the coefficient of x , which is 1 , divide by two, giving 1/2 , and finally square it giving 1/4

Add 1/4 to both sides of the equation :

On the right hand side we have :

20 + 1/4 or, (20/1)+(1/4)

The common denominator of the two fractions is 4 Adding (80/4)+(1/4) gives 81/4

So adding to both sides we finally get :

x2-x+(1/4) = 81/4

Adding 1/4 has completed the left hand side into a perfect square :

x2-x+(1/4) =

(x-(1/2)) • (x-(1/2)) =

(x-(1/2))2

Things which are equal to the same thing are also equal to one another. Since

x2-x+(1/4) = 81/4 and

x2-x+(1/4) = (x-(1/2))2

then, according to the law of transitivity,

(x-(1/2))2 = 81/4

We'll refer to this Equation as Eq. #4.2.1

The Square Root Principle says that When two things are equal, their square roots are equal.

Note that the square root of

(x-(1/2))2 is

(x-(1/2))2/2 =

(x-(1/2))1 =

x-(1/2)

Now, applying the Square Root Principle to Eq. #4.2.1 we get:

x-(1/2) = √ 81/4

Add 1/2 to both sides to obtain:

x = 1/2 + √ 81/4

Since a square root has two values, one positive and the other negative

x2 - x - 20 = 0

has two solutions:

x = 1/2 + √ 81/4

or

x = 1/2 - √ 81/4

Note that √ 81/4 can be written as

√ 81 / √ 4 which is 9 / 2

User Jason Ayer
by
8.1k points
5 votes

Answer:

Factors of x are 0, 5, and -4.

Explanation:

⇒ x³ = x² + 20x

⇒ x³ - x² - 20x = 0

⇒ x (x² - x - 20) = 0

⇒ x ( x² - 5x + 4x - 20) = 0

⇒ x ( x ( x - 5) + 4 ( x - 5)) = 0

⇒ x (x - 5) (x + 4) =0

x = 0, 5, and -4

User Georgy Pashkov
by
8.0k points